Інноваційний аудит економічної діяльності підприємства та складання звітності - Одношевна, Ольга Олександрівна; Odnoshevna, Olga (Економічна академія Д. А. Ценова, Свіштов Болгарія, 2023)
В статті представлені особливості здійснення інноваційного аудиту економічної діяльності підприємств з огляду на сучасні вимоги у законодавстві. Так, представлений огляд інформації, який стосується змін саме на початок 2023 року. Дані зміни, включають необхідність запровадження у виробничо-господарську діяльність електронних продуктів проведення аудиторської перевірки на базі розробленою державою платформи «Є-аудит». Представлена платформа включає необхідність обов'язкового подання SAF-T UA для усіх великих платників податків. Дана програма передбачає експорт звітних даних про економічну діяльність окремо взятого підприємства на конкретну дату. Використання SAF-T UA дозволяє значно полегшити, прискорити та оптимізувати роботу по перевірці діяльності окремо взятого підприємства, включаючи перевагу проведення перевірки перед поданням звіту до державних органів. The article reveals the modern requirements of today's financial and economic activities of most domestic enterprises and organizations, which involve the use of modern automated means of communication through established electronic document management platforms. Let's note, that the direct level of efficiency of an individual enterprise depends on the chosen system of automation of the production process. The modern market offers many electronic products that can satisfy the needs of any consumer, taking into account the specifics of his activity. That’s why, when you will choose an individual electronic platform, it is advisable to conduct a thorough monitoring of electronic product offers presented on the market and choose the one that would best meet the requirements of an individual enterprise. It should be stated that a suitable automation mode will allow to increase the level of farm efficiency several times. During writing the article, was analyzed the works of many domestic and foreign authors. After carefully monitoring the offers on the electronic products market, we suggest stopping at the electronic platform «Sonata». This product includes the full range of opportunities for conducting financial activities, compiling and submitting reports to state authorities. Sonata also provides an opportunity to easily switch from another electronic platform. You can simply import the necessary information. In the proposed program, it is possible to choose the taxation system, the list of necessary reports, the list of necessary government agency, the list of partners and employees. With the help of the calendar module, you can set a reminder that it is time to make and send the necessary report. This function is very useful as it minimizes the possibility of late reporting. The function of dividing counterparties into subspecies is very convenient, so they can be divided into buyers, suppliers, creditors and others. It should be concluded that the use of the electronic program "Sonata" will allow any modern enterprise to reach a new level of work. Namely, to conduct one's activity easily, in a timely manner and in accordance with the laws of Ukraine.
Innovative audit of the economic activity of the enterprise and reporting
Keywords: економічна діяльність; economic activity; інноваційний аудит; innovative audit; електронна платформа; electronic platform; «Є-аудит»; "E-audit"; звітність; reporting